2013
DOI: 10.1158/1535-7163.mct-13-0011
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effects of Continued Mitogen-Activated Protein Kinase Pathway Inhibition following Acquired Resistance to BRAF and/or MEK Inhibition in Melanoma

Abstract: Inhibitors of the mitogen-activated protein kinases (MAPK), BRAF, and MAP-ERK kinase (MEK) induce tumor regression in the majority of patients with BRAF-mutant metastatic melanoma. The clinical benefit of MAPK inhibitors is restricted by the development of acquired resistance with half of those who benefit having progressed by 6 to 7 months and long-term responders uncommon. There remains no agreed treatment strategy on disease progression in these patients. Without published evidence, fears of accelerated dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 47 publications
4
81
1
3
Order By: Relevance
“…For instance, it is helpful to add a Ras inhibitor while keeping the patient on the Raf inhibitor with which they were already being treated. This was partially confirmed when the clinical benefits of continued ERK1/2 sub-pathway inhibition following cancer progression were demonstrated (77). However, several preclinical models revealed that discontinuation of a drug based on the inhibitors or intermittent scheduling may also slow tumor growth (78).…”
Section: Discussionmentioning
confidence: 86%
“…For instance, it is helpful to add a Ras inhibitor while keeping the patient on the Raf inhibitor with which they were already being treated. This was partially confirmed when the clinical benefits of continued ERK1/2 sub-pathway inhibition following cancer progression were demonstrated (77). However, several preclinical models revealed that discontinuation of a drug based on the inhibitors or intermittent scheduling may also slow tumor growth (78).…”
Section: Discussionmentioning
confidence: 86%
“…The clarified cell suspension was maintained in DMEM/10% FCS containing penicillin and streptomycin (Gibco). Contaminating fibroblasts were removed by treating cultures with 100 mg ml À 1 G418 (Gibco) as required 58 . Cells were grown in DMEM with 10% FCS and glutamine (Gibco BRL) and cultured in a 37°C incubator with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacological growth inhibition assays were performed using 1-2 Â 10 3 cells per well in 96-well plates and 24 h after seeding, serial dilutions of each inhibitor were added to cells. Cells were incubated for an additional 72 h and cell viability was measured using the Cell proliferation Aqueous MTS assay (Promega) on a VICTOR 2 Multilabel counter (PerkinElmer) 58 .…”
Section: Methodsmentioning
confidence: 99%
“…Cell culture, constructs, and lentivirus transductions SKMel28 and A375 melanoma cells were obtained from Prof. P. Hersey (Kolling Institute, University of Sydney, New South Wales) and short-term cultures were established from a subset of patients as previously described (30). Cells were grown in Dulbecco's Modified Eagle Medium (DMEM) with 10% FBS and glutamine (Gibco-BRL) and cultured in a 37 C incubator with 5% CO 2 .…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Total cellular proteins were extracted and analyzed as previously described (30). Western blots were probed with the following antibodies: total ERK (137F5; Cell Signaling Technology), phosphorylated ERK (E-4; Santa Cruz Biotechnology), MYC (A-14; Santa Cruz Biotechnology), FLAG (Sigma-Aldrich), MEK1/2 (L38C12; Cell Signaling Technology), ATM (D2E2; Cell Signaling Technology) and b-actin (AC-74; Sigma-Aldrich).…”
Section: Western Blottingmentioning
confidence: 99%